2008
DOI: 10.1128/ec.00020-08
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Recombination in Mixed-Mating-Type and α-Only Populations of Cryptococcus gattii Sourced from Single Eucalyptus Tree Hollows

Abstract: Disease caused by the pathogenic yeast Cryptococcus gattii begins with the inhalation of an infectious propagule. As C. gattii is heavily encapsulated, this propagule is most likely to be a basidiospore. However, most C. gattii strains are infertile in laboratory crosses, and population studies indicate that recombination and dispersal are very restricted. In addition, strains of the ␣ mating type predominate, which would not be expected in a mating population. C. gattii comprises four genetically distinct mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 58 publications
1
65
1
Order By: Relevance
“…First, the discovery and characterization of ␣AD␣ hybrids produced by the mating of two ␣ isolates of different serotypes (A and D) provide definitive evidence that unisexual mating has occurred in nature (164). Second, recent studies of C. gattii populations from tree hollows in Australia provided evidence that recombination is occurring within populations that are exclusively of the ␣ mating type (264). Third, population genetic studies of C. neoformans isolates from tree hollows in India provide evidence for recombination in otherwise ␣ unisexual populations, and one parsimonious hypothesis is that this involves unisexual reproduction (105).…”
Section: Same-sex Mating In Cryptococcus Speciesmentioning
confidence: 99%
“…First, the discovery and characterization of ␣AD␣ hybrids produced by the mating of two ␣ isolates of different serotypes (A and D) provide definitive evidence that unisexual mating has occurred in nature (164). Second, recent studies of C. gattii populations from tree hollows in Australia provided evidence that recombination is occurring within populations that are exclusively of the ␣ mating type (264). Third, population genetic studies of C. neoformans isolates from tree hollows in India provide evidence for recombination in otherwise ␣ unisexual populations, and one parsimonious hypothesis is that this involves unisexual reproduction (105).…”
Section: Same-sex Mating In Cryptococcus Speciesmentioning
confidence: 99%
“…AFLP analysis of clinical isolates revealed that they are geographically restricted, highly clonal, and of low fertility (53,116,117). Subsequent extensive testing of isolates from single tree hollows by AFLP analysis revealed that recombination is occurring in both MATa and MAT␣ or MAT␣-only populations (118). Isolates of VGII from Australia are highly fertile and recombining (117), with a recent study also suggesting recombination within the MAT␣-MATa population, especially in Western Australia (88).…”
Section: Reproduction In Naturementioning
confidence: 99%
“…Eucalypts are in fact only one of Ͼ50 different species of tree that can provide an ecological niche for C. gattii (106)(107)(108)(109)(110). Environmental isolates have been obtained from Africa (33,(110)(111)(112), Asia (76,77,108), Australia (26,110,(113)(114)(115)(116)(117)(118), Europe (110,119,120), North America (38,110,121), and South America (122). In addition, it has been shown that plant material promotes fertility (108,(123)(124)(125) and may render C. gattii strains more pathogenic (125).…”
Section: Environmental Studiesmentioning
confidence: 99%
“…grubii and C. gattii strains do not reproducibly undergo monokaryotic fruiting under laboratory conditions. Population genetic studies provided evidence that they do so in nature (4,21,36,49), but this remains to be established under defined laboratory conditions.…”
mentioning
confidence: 99%
“…However, if spores are the infectious propagule, and spores are produced by mating between a and ␣ cells, how and where would this occur in the largely ␣ unisexual population? A potential resolution was the discovery that ␣ isolates can produce hyphae, basidia, and basidiospores via monokaryotic fruiting (11,54), a modified sexual cycle that requires only one of the two mating types (4,12,21,(33)(34)(35)(36)49). This might be a route by which infectious propagules are produced in nature; however, serotype A C. neoformans var.…”
mentioning
confidence: 99%